Chitosan-thiobarbituric acid: a superadsorbent for mercury - Bhatt, Rahul; Kushwaha, Shilpi; Bojja, Sreedhar; Padmaja, P. (ACS Omega, 2018)
In the present investigation, chitosan (CH) as supramolecularly cross-linked with thiobarbituric acid to form CT. CT was well characterized by UV, scanning electron microscopy-energy-dispersive X-ray analysis, Fourier trans form infrared, NMR, differential scanning calorimetry, thermogravimetric analysis, and X-ray difTraction analyses, and its adsorption potential for elemental mercury (Hg-0), inorganic mercury (Hg2+), and methyl mercury (CH3Hg+) was investigated. Adsorption experiments were conducted to optimize the parameters for removal of the mercury species under study, and the data were analyzed using Langmuir, Freundlich, an Temkin adsorption isotherm models. CT was found to have high adsorption capacities of 1357.69, 2504.86, and 2475.38 rng/g for Hg-0, Hg2+, and CH3Hg+, respectively. The adsorbent CT could be reused up elemental mercury using 0.01 N thiourea, inorganic mercury using 0.01 N perchloric acid, and methyl to three cycles by eluting mercury with 0.2 N NaCl.